18F-FDG PET/CT in preoperative staging of vulvar cancer patients: is it really effective?. Issue 38 (September 2017) - Crivellaro, Cinzia; Guglielmo, Priscilla; De Ponti, Elena; Elisei, Federica; Guerra, Luca; Magni, Sonia; La Manna, Maria; Di Martino, Giampaolo; Landoni, Claudio; Buda, Alessandro
Abstract : Abstract: The aim of this study was to assess the role of 18F-FDG PET/CT in preoperative staging of vulvar cancer patients. 29 pts (69 years, range 51–88) with vulvar cancer (clinical apparent stage I-II), underwent preoperative FDG-PET/CT scan followed by radical vulvectomy and bilateral (or monolateral in case of tumor >2 cm from midline) inguinal lymphadenectomy ± sentinel node biopsy. PET/CT images were analyzed in consensus and correlated to histological findings according to a pt-based and a groin-based analyses. SUVmax of the nodal uptake of each inguinal area (if present) was calculated and correlated to histological findings. The presence of distant metastases was also considered and confirmed. PET/CT analysis in consensus resulted negative at the inguinal LN level in 17 pts (10 true negative, 7 false negative) and positive in 12 pts (7 true positive, 5 false positive). Incidence of LN metastases resulted 48%. On pt-based analysis, sensitivity, specificity, accuracy, and negative and positive predictive value of PET/CT in detecting LN metastases were 50%, 67%, 59%, 59%, and 58%, respectively. On a groin-based analysis, considering overall 50 LN-sites, sensitivity, specificity, accuracy, and negative and positive predictive value of PET/CT were 53%, 85%, 73%, 67%, and 76%, respectively. The mean value of SUVmax was 6.1 (range 0.7–16.2) for metastatic nodes, whereas 1.6 (range 0.7 – 5.4) for negative lymph-nodes ( P = .007). PET/CT detected pelvic (n = 1) and both pelvic/paraortic (n = 1) nodal metastases. In clinical early stage vulvar cancer FDG PET/CT showed low sensitivity and moderate specificity for N-staging; therefore, it is not an accurate tool for the nodal status assessment. PET/CT may not be cost-effective in detecting the rare event of distant metastases, but further studies are needed.